2013
DOI: 10.1371/journal.pone.0083665
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Model for Knee Joint Replacement in Older Women

Abstract: Knee replacement (KR) is expensive and invasive. To date no predictive algorithms have been developed to identify individuals at high risk of surgery. This study assessed whether patient self-reported risk factors predict 10-year KR in a population-based study of 1,462 women aged over 70 years recruited for the Calcium Intake Fracture Outcome Study (CAIFOS). Complete hospital records of prevalent (1980-1998) and incident (1998-2008) total knee replacement were available via the Western Australian Data Linkage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Non-imaging variables were screened for among studies and reviews detailing risk factors for knee OA progression and TKR onset [21][22][23][33][34][35][36] . Variables such as KL grade known to be deducible directly from MRI images and radiographs were not considered.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Non-imaging variables were screened for among studies and reviews detailing risk factors for knee OA progression and TKR onset [21][22][23][33][34][35][36] . Variables such as KL grade known to be deducible directly from MRI images and radiographs were not considered.…”
Section: Datamentioning
confidence: 99%
“…A few studies have leveraged random forest regression, Cochran-Armitage tests for trend, and t-tests to identify demographic, general health, and physical examination measurements that most strongly correlate with TKR or total joint arthroplasty (TJA) 20,21 . Others have taken these efforts further, using techniques such as multiple regression and multivariate risk prediction models to predict TKR outright 22,23 . To our knowledge, only one group has developed a predictive model of TKR that accepts image inputs, attaining performance that surpasses that of models using only clinical and demographic information 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found relationships between TKR and sex, BMI, and other risk factors in OAI 12 and targeted analyses of high-risk sub-populations. 43 F I G U R E 7 Mean ROC graphs for 5 years TKR predictive model. The base model includes only the demographic and clinical variables while the added T 2 model has T 2 averages as well.…”
Section: T 2 Values and Tkrmentioning
confidence: 99%
“…Of the 30 studies identified in the literature review, four related to predicting TKR [ [11] , [12] , [13] , [14] ], six related to predicting response/non-response to TKR [ 8 , [15] , [16] , [17] , [18] , [19] ] and the remainder reported associations with TKR (12 studies) [ [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] ] and response/non-response to TKR (eight studies) [ [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] ].…”
Section: Introductionmentioning
confidence: 99%
“…Of the studies predicting TKR, only one reported on the performance of the model (c-statistic ​= ​0.79) [ 11 ], only one addressed missing data [ 14 ], and the statistical methods used to develop the models were not well reported in two of the studies [ 11 , 12 ]. Factors found to be predictive of TKR included measures of knee pain and physical function, use of medication for knee pain, Knee Outcome Survey-Activities of Daily Living Subscale (KOS-ADLS), 36-Item Short Form Health Survey (SF-36) general health subscale score, willingness to undergo TKR, seeing a healthcare provider for arthritis, knee osteoarthritis grade and 12-Item Short Form Survey (SF-12) mental component score [ [11] , [12] , [13] , [14] ].…”
Section: Introductionmentioning
confidence: 99%